Human rights and schooling : an ethical framework for teaching for social justice - Osler, Audrey (2016)
Most of the struggles for equitable schooling, including multicultural curricula and culturally responsive teaching, have largely taken place on a local or national stage, with little awareness of how international human rights standards might support these struggles. Human Rights and Schooling explores the potential of human rights frameworks to support grassroots struggles for justice and examines the impact that human rights and child rights education can make in the lives of students, including the most marginalized. The author, Audrey Osler, examines the theory, research, and practice linking human rights to education in order to broaden the concept of citizenship and social studies education. Bringing scholarship and practice together, the text uses concrete examples to illustrate the links between principles and ideals and actual efforts to realize social justice in and through education. Osler anchors her examination of human rights in the U.N. Convention on the Rights of the Child, as well as the U.N. Declaration on Human Rights Education and Training. -- from back cover.
Human rights education, politics, and power -- The right to human rights education -- Intersectionality, human rights, and identities -- Narrative in teaching for justice and human rights -- Human rights, education, and the nation -- Human rights, peace, and conflict -- Child rights: The heart of the project -- Reimagining a cosmopolitan future.
Includes bibliographical references (pages 151-168) and index.
Keywords: Human rights -- Study and teaching; Social justice -- Study and teaching; Democracy and education; Democracy and education; Human rights -- Study and teaching; Social justice -- Study and teaching